2021
DOI: 10.1186/s13037-020-00279-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased perioperative mortality for femoral neck fractures in patients with coronavirus disease 2019 (COVID-19): experience from the United Kingdom during the first wave of the pandemic

Abstract: Background The coronavirus disease 19 (COVID-19) pandemic has presented modern healthcare with an unprecedented challenge. At the peak of the pandemic, trauma and orthopaedic services at our institutions undertook internal restructuring, diverting resources to frontline medical care. Consequently, we sought to assess the impact on the elderly and comorbid patients presenting with femoral neck fractures, with a particular focus on 30-day mortality, length of stay, multidisciplinary team involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…Outbreaks of COVID-19 at select skilled nursing facilities in our catchment area may have affected public perception of the safety of these facilities and decrease patient/patient family desire to be discharged to them. This contrasts with the findings of Wright et al [ 43 ], where 47% of hip fracture patients required increased support or a higher level of care at discharge. A similar study in the United Kingdom found patients were less likely to return home after hip fracture surgery during the pandemic [ 44 ].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Outbreaks of COVID-19 at select skilled nursing facilities in our catchment area may have affected public perception of the safety of these facilities and decrease patient/patient family desire to be discharged to them. This contrasts with the findings of Wright et al [ 43 ], where 47% of hip fracture patients required increased support or a higher level of care at discharge. A similar study in the United Kingdom found patients were less likely to return home after hip fracture surgery during the pandemic [ 44 ].…”
Section: Discussioncontrasting
confidence: 95%
“…This aligns with the majority of studies conducted to date, which suggest that time-to-surgery for hip fracture patients has not changed during the COVID-19 pandemic [ 30 , 31 , 35 , 36 , 37 ]. Changes to timing of other aspects of the healthcare system have been posited to impact outcomes, such as changes in time to orthogeriatric or multidisciplinary care [ 37 , 43 ]. Arafa et al [ 38 ] found an increase in anesthesia preparation and induction time, although this was only significant in patients who were positive for COVID-19 compared to historical controls.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the release of a "cytokine storm" and activation of the complement system which promotes a systemic environment of hyperinflammation and hypercoagulability (8)(9)(10)(11)(12)(13)(14)(15). These pathophysiological changes may contribute to the increased perioperative risk of thromboembolic complications and the high postoperative mortality observed in surgical patients with COVID-19 (16)(17)(18)(19)(20). The current special edition in Frontiers in Surgery was designed to improve the understanding of the immune-mediated pathophysiological events that lead to adverse outcomes in the vulnerable population of COVID-19 patients undergoing surgical procedures.…”
Section: Editorial On the Research Topic The Impact Of Covid-19 On Im...mentioning
confidence: 99%
“…During the first wave of the pandemic, from march to september 2020, early small studies investigating the effect of covid-19 on hip fracture mortality found a significant increase in mortality, ranging from 11.7% to 40%. [6][7][8][9][10][11][12][13] our previously published regional audit of 1,633 patients conducted in the North West of England, also conducted in the first wave, found that 30-day mortality had increased from 6.8% (2019 control) to 35.6% in covid-19 positive patients. 14 similarly, meta-analyses found mortality rates of 32.6% and 36%, respectively.…”
Section: Introductionmentioning
confidence: 99%